Jumonji AT-rich interactive domain 1B overexpression is associated with the development and progression of glioma - FANG, LIPING (Int J Mol Med, 2016)
Previous studies have suggested that jumonji AT-rich interactive domain 1B (JARID1B) plays an important role in the genesis of some types of cancer, and it is therefore considered to be an important drug target protein. Although the expression of JARID1B has been researched in some types of cancer, little is known about JARID1B expression in glioma and its function in the tumorigenesis of gliomas. In the present study, we examined the expression of JARID1B in glioma. In addition, RT-PCR, western blot analysis and immunohistochemical analysis were performed using glioma tissue samples and the results revealed that JARID1B expression increased according to the histological grade of glioma. However, in the normal brain tissue samples JARID1B expression was barely detected. Kaplan-Meier analysis revealed that higher JARID1B expression in patients with glioma was associated with a poorer prognosis. The overexpression of JARID1B stimulated the proliferation and migration of glioma cells as well as sphere formation, whereas suppressing the expression of JARID1B produced opposite effects. The overexpression of JARID1B increased the tumorigenicity of glioma cells in vivo in a nude mouse xenograft model of glioma. Moreover, the activation of phosphorylated (p-)Smad2 contributes to JARID1B-induced oncogenic activities. These findings suggest that JARID1B is involved in the pathogenesis of glioma, and that the downregulation of JARID1B in glioma cells may be a therapeutic target for the treatment of patients with glioma.